2019
DOI: 10.3390/antibiotics8040236
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Potentially New Antibiotics from Mangrove Actinobacteria in Maowei Sea by Combination of Multiple Discovery Strategies

Abstract: Rediscovery of known antibiotics from actinobacteria, especially Streptomyces, has become a bottleneck issue. Nowadays, more specific identification and dereplication could be acquired by a combination of modern analytic techniques with various databases. In this study, 261 actinobacterial strains were isolated from 8 mangrove soil samples by culture-dependent method. A total of 83 strains were selected to evaluate antibacterial activities and mechanisms by disc diffusion method and a unique double fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…To gain a comprehensive understanding of chemical diversity in the cultural broth of strain 16Sb2-4, UPLC-QTof-MS/MS-based dereplication analyses coupled with molecular networking were performed prior to the metabolites isolation. Many researches have reported the successful application of molecular networking for effective chemical dereplication and novel metabolite discovery ( Duncan et al, 2015 ; Kleigrewe et al, 2015 ; Esposito et al, 2017 ; Nothias et al, 2018 ; Lu et al, 2019 ), especially in our latest research on endophytic actinobacteria from psammophytes in Taklamakan desert, it has successfully contributed to the discovery of two new griseoviridin-type antibiotics from the fermentation broth of an endophytic Streptomyces strain ( Wang et al, 2020a ). In the present study, four families of bioactive compounds were observed and predicted from the crude extract of strain 16Sb2-4, including lipopeptides, cyclic depsipeptides, 22-membered macrolactams, and 16-membered macrolides.…”
Section: Discussionmentioning
confidence: 99%
“…To gain a comprehensive understanding of chemical diversity in the cultural broth of strain 16Sb2-4, UPLC-QTof-MS/MS-based dereplication analyses coupled with molecular networking were performed prior to the metabolites isolation. Many researches have reported the successful application of molecular networking for effective chemical dereplication and novel metabolite discovery ( Duncan et al, 2015 ; Kleigrewe et al, 2015 ; Esposito et al, 2017 ; Nothias et al, 2018 ; Lu et al, 2019 ), especially in our latest research on endophytic actinobacteria from psammophytes in Taklamakan desert, it has successfully contributed to the discovery of two new griseoviridin-type antibiotics from the fermentation broth of an endophytic Streptomyces strain ( Wang et al, 2020a ). In the present study, four families of bioactive compounds were observed and predicted from the crude extract of strain 16Sb2-4, including lipopeptides, cyclic depsipeptides, 22-membered macrolactams, and 16-membered macrolides.…”
Section: Discussionmentioning
confidence: 99%
“…8P21H-1, and the speculation about the existence of five putative new quinoxaline-type antibiotics in the fermentation broth of Streptomyces sp. B475 [ 37 , 38 ]. Comparison of traditional untargeted or bioassay-guided approaches, molecular networking is fast, requiring minimal time and sample material.…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces tanashiensis isolated from mangrove forest soil Maowei, China, it had the ability of antibacterial activity to Bacillus cereus (Lu et al, 2019). According to Johnson and Dietz (1968),Streptomyces tanashiensis synthesized and secrete out to luteomycin (antifungal), mithramycin (anticancer), phosphoramidon (inhibition of enzyme thermolysin from Bacillus spp.)…”
Section: Streptomyces Parvulusmentioning
confidence: 99%